Demineralization of Silica-Rich Agar Processing Residues via Hydrofluoric Acid Leaching for Organic Fraction Enrichment - Andi Firdaus Sudarma; Edy Hartulistiyoso; Y. Aris Purwanto; Leopold Oscar Nelwan; Obie Farobie; Hendri; Harri Junaedi; Edy Herianto Majlan (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2026)
Agar solid waste (ASW) is a silica-rich industrial residue generated during agar extraction that contains organic residue mixed with mineral filtration aids such as Celite (diatomaceous earth) and perlite. Its high ash content and low organic fraction limit its direct utilization as a biomass-derived fuel. This study investigated hydrofluoric acid (HF) leaching as a demineralization pretreatment to reduce silica-rich minerals and improve the physicochemical quality of ASW. Two ASW samples obtained from different agar-processing plants, namely ASW-Celite (contain Celite) and ASW-Perlite (contain perlite), were treated using 10 wt% HF at a solid-to-liquid ratio of approximately 1:12. The treated samples were characterized using XRF, ICP-MS, FTIR, ultimate analysis, and proximate analysis. HF leaching caused substantial mass reduction, with solid yields of 24.99% for ASW-Celite-HF and 48.9% for ASW-Perlite-HF. Ash content decreased from 85.84 to 44.99 wt% in ASW-Celite and from 77.10 to 24.83 wt% in ASW-Perlite. XRF analysis confirmed significant silica removal, particularly in ASW-Celite, where SiO₂ decreased from 96.94 to 21.30%. ICP-MS further showed the reduction of several ash-forming and environmentally relevant elements, including Cr, Ni, Cu, Zn, Cd, P, S, Cl, Mn, and Fe. HF treatment also enriched the organic fraction, increasing carbon content from 4.69 to 12.52 wt% in ASW-Celite and from 9.83 to 16.10 wt% in ASW-Perlite. The HHV of ASW-Celite improved from 1.91 to 6.52 MJ/kg, whereas ASW-Perlite decreased from 4.80 to 3.19 MJ/kg due to its high oxygen content after treatment. These findings demonstrate that HF leaching effectively reduces silica-rich minerals in ASW, although further deoxygenation is required to improve its fuel quality for bioenergy applications.